Does social desirability compromise self-reports of physical activity in web-based research? - Göritz Anja S; Crutzen Rik (BMC, 2011)
Abstract Background This study investigated the relation between social desirability and self-reported physical activity in web-based research. Findings A longitudinal study (N = 5,495, 54% women) was conducted on a representative sample of the Dutch population using the Marlowe-Crowne Scale as social desirability measure and the short form of the International Physical Activity Questionnaire. Social desirability was not associated with self-reported physical activity (in MET-minutes/week), nor with its sub-behaviors (i.e., walking, moderate-intensity activity, vigorous-intensity activity, and sedentary behavior). Socio-demographics (i.e., age, sex, income, and education) did not moderate the effect of social desirability on self-reported physical activity and its sub-behaviors. Conclusions This study does not throw doubt on the usefulness of the Internet as a medium to collect self-reports on physical activity.